Clinical Effect of Endovascular Treatment on Blood Pressure and Kidney Function for Hypertensive Patients with Renal Artery Stenosis. (August 2013) - He, Yuxiang; Liu, Yang; Wang, Mo; Sun, Yan; Dong, Dianning; Yuan, Hai; Wu, Xuejun; Chong, Zhenyue; Jin, Xing
<x xml:space="preserve">Abstract</x> The objective of this study was to evaluate the clinical effect of endovascular treatment on postoperative blood pressure (BP) control and kidney function of hypertensive patients with renal artery stenosis (RAS). Between January 2004 and December 2011, RAS was diagnosed in 120 renal arteries from 115 hypertensive patients. Preoperative and postoperative BPs and glomerular filtration rate (GFR) were monitored. Postoperative oral antiplatelet and antihypertensive agents were administered. Clinical follow-up was available for all patients for at least 6 months. Balloon angioplasty was performed successfully in 110 patients, and stents were deployed in 94 renal arteries from 89 patients. Hypertension was cured and lessened in 19 and 61 patients, respectively. Blood pressure was stable and worsened in 26 and 9 patients, respectively. The renal function was improved and stable in 23 patients and 57 patients, respectively. Deterioration of renal function was observed in 11 patients. Doppler ultrasound after discharge revealed 87 patent renal arteries and fixed stents in 82 patients 6 months after procedure. Balloon angioplasty and stent deployment are effective and feasible procedures for patients with RAS that help in controlling BP and improving renal function moderately.